Handbook of mechanical ventilation - Kumar, B. Umesh; Chacko, José (New Delhi : Japee Brothers Medical Publishers, 2011)
Written in a clear and lucid style without getting bogged down in trivia, this book covers about initiation and monitoring during mechanical ventilation, respiratory pathophysiology, airway management and weaning patients from mechanical ventilation as a quick guide in a refreshingly readable manner
Trata sobre el inicio y el seguimiento durante la ventilación mecánica, la fisiopatología respiratoria, el manejo de las vías respiratorias y el destete de los pacientes de la ventilación mecánica como una guía rápida de una manera amena y amena.
Contents Chapter 1: Basic Principles of Mechanical Ventilation Chapter 2: Pulmonary Anatomy and Physiology Chapter 3: Respiratory Pathophysiology 4: Arterial Blood Gas Analysis Chapter 5: Indication for Mechanical Ventilation y otros 9 capítulos más
Keywords: RESPIRACIÓN ARTIFICAL; VENTILACIÓN MÉCANICA; ARTIFICIAL RESPIRATION